Efeito de 12 semanas de exercícios físicos multimodais no controle da pressão arterial sanguínea das pessoas idosas hipertensas do projeto vida ativa - UFT - Curcino, Eliamaria Ribeiro (Universidade Federal do Tocantins, 2024)
The present study aimed to verify the effect of 12 weeks of multimodal physical exercise on blood pressure control in hipertensive old people participating in the Active Life Project-UFT. Based on this objective, we propose a reflection on the paths taken by Physical Education and its relationship with health. Methodologically, it is configured as a field study, of bibliographic, field and descriptive character, of a quantitative nature. Eight elderly females and three elderly males participating in the aforementioned project in 2023 participated in the research. The information collected was obtained by measuring the blood pressure values of the participants at baseline and after 12 weeks of intervention with multimodal exercises. The collection recommendations of the WHO (2020) were followed, and blood pressure was measured in a reserved room within the Federal University of Tocantins, using the OMRON / HEM-7320 automatic arm blood pressure measuring device/monitor. Descriptive data were presented as percentages, median (Md) and interquartile range (IQR). The Shapiro-Wilk test showed a non-normal distribution, so for the inferential data we used the Wilcoxon Matched-Pairs test (non-parametric) using the IBM SPSS Statistics for Windows Version 22.0 (IBM Corp., Armonk, NY, with a significance value of p <0.05. The results concluded that, for the population studied, there was a hypotensive effect after 12 weeks of intervention with multimodal physical exercises, on systolic blood pressure values with a median of 140mmHg (Md) at baseline to 110mmHg (Md) after intervention with a p=0.004 value.